2. Periictal activity in cooled asphyxiated neonates with seizures. Issue 9 (September 2016) - Major, Philippe; Lortie, Anne; Dehaes, Mathieu; Lodygensky, Gregory Anton; Gallagher, Anne; Carmant, Lionel; Birca, Ala
Abstract : Seizures are common and worsen the outcome in critically ill neonates. Predicting seizure recurrence could allow individualizing antiepileptic treatment and improving the outcome. To identify EEG signatures of seizure recurrence, we investigated periictal spectral power and electrographic characteristics of seizures in five consecutive asphyxiated neonates under continuous EEG monitoring. All patients had high seizure burden while undergoing hypothermic neuroprotection. Two neonates had recurrence of seizures on rewarming. Spectral power analysis of fifteen artifact-free consecutive ictal events demonstrated, in all neonates, a significant increase in overall spectral power from the interictal to preictal and ictal periods ( p  < 0.01). Delta frequency power increase was consistently observed in all patients. Alpha power increase was more pronounced in the two patients with recurrence of seizures on rewarming and significant when comparing both interictal-to-preictal and interictal-to-ictal periods. In these two patients, preictal and ictal alpha activity displayed a regional, hemispheric or even diffuse distribution contrasting with the focal seizure onset. This distinct alpha activity preceding ictal onset could represent a biomarker of propensity for seizure recurrence. Future studies should be performed to confirm whether quantitative periictal characteristics and electrographic features allow predicting the risks of seizure recurrence in asphyxiated hypothermic neonates and other critically ill patients.